Tensile Behaviour and Durability Issues of Engineered Cementitious Composites with Rice Husk Ash - Righi,Débora Pedroso (2017)
ABSTRACT The Engineered Cementitious Composites (ECC) is a special type of High Performance Fibre Reinforced Cementitious Composite (HPFRCC) characterized by a high tensile ductility with a 2% maximum volume of micro fibres. ECC has a tensile strain-hardening performance that leads to multiple cracking behaviour, thus providing the high ductility to the concrete. One of the main applications of ECC is as structural reinforcement in the construction or rehabilitation of rigid and flexible pavements. In order to adapt the ECC to the Brazilian environment, polypropylene fibres have been used instead to PVA fibres. Moreover, rice husk ash (RHA) has also been used as a partial replacement to cement, aiming to produce an environmentally friendly and a more economically viable version of the ECC. This work presents the results obtained for ECC mixtures containing 10%, 20% and 30% (by volume) of non-processed rice husk ash, as a replacement to cement. An experimental study has been carried out to investigate the tensile behavior and durability issues of these ECCs. The results indicate that the use of RHA is technically viable and that the replacement of 30% cement by RHA leads to the most promising performance in terms of high ductility, resistance to crack propagation, decrease in the water absorption and voids content and heat at hydration.